A High Strength Ti–SiC Metal Matrix Composite1 . Issue 7 (22nd March 2017) - Rahman, Khandaker Mezanur; Vorontsov, Vassili A.; Flitcroft, Stephen. M.; Dye, David
Abstract : A SiC reinforced Ti‐5Al‐5Mo‐5V‐3Cr matrix metal matrix composite is developed. Monolithic blocks of alloy are hot rolled via pack rolling to produce foils for MMC panel fabrication. These are consolidated using hot isostatic pressing and solution treated and aged for optimum strength. The panels exhibited a strength of 2 GPa in tension and 3.5 GPa in compression, compared to the aerospace steel 300M, which has a tensile strength of 1.69 GPa. The fatigue performance of the material exceeded that of MMCs developed using Ti‐21S or Ti‐6Al‐4V matrices. Finally, the reaction zone between the SiC and matrix is examined, revealing the presence of TiC. Abstract : A metal matrix composite is produced using a titanium matrix and silicon carbide reinforcement. A cheaper foil fibre foil layup method is used. The resultant material had a tensile strength in excess of 2GPa with excellent fatigue properties.